2009
DOI: 10.1590/s1516-14392009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of polyamide 6/Brazilian clay nanocomposites

Abstract: and also to evaluate the structure and mechanical properties of the obtained nanocomposites. Experimental MaterialsPolyamide 6 (PA6) was supplied by Rhodia ® /Brazil. The used pristine clay was Na-Montmorillonite clay (MMT, Boa Vista/Paraíba, Northeast of Brazil) supplied by Bentonit União Nordeste with a cation exchange capacity (CEC) of 90 meq.100 g -1 and the interlayer spacing (d 001 ) obtained by XRD was 12.74 Å. MMT was dried at 60 °C for 48 hours prior to use. The used quaternary ammonium salts for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…It is interesting to notice that the nanocomposites patterns presented the same behavior regardless the processing variables used. These results are consistent with other works reported in the literature 15,16 .…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 94%
See 1 more Smart Citation
“…It is interesting to notice that the nanocomposites patterns presented the same behavior regardless the processing variables used. These results are consistent with other works reported in the literature 15,16 .…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 94%
“…They present morphologies composed of exfoliated clay lamellae and well distributed in the polymer matrix. Similar results were observed in the literature 5,10,16 with nanocomposites obtained from commercial clays These images corroborate the results of X-ray diffraction.…”
Section: Transmission Electron Microscopy (Tem)supporting
confidence: 92%
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 94%
“…Probably, the presence of the clay crystalline behavior altered of PA6. However, when small percentages of clay are added to polymer matrices, the degree of crystallinity Xc, increases the nanocomposite which may demonstrate a nucleating effect of the clay 34,35,49 . The SEM images of the top surface and cross section of pure PA6 membranes and their hybrids 1, 3, 5% w/w of MMT, adding 10% w/w CaCl 2 , are shown in figures from 3 to 6.…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…de processamento adequados, a fim de se obter nanocompósitos intercalados e/ou parcialmente esfoliados. Estes resultados foram confirmados por meio de vários trabalhos já desenvolvidos e apresentados [6,[16][17][18] .…”
Section: Difração De Raio X (Drx)unclassified